Bridging the gap: exploring students’ needs, knowledge, and preferences for delivering comprehensive sexuality education in Sierra Leone - Regina Mamidy Yillah; Rajeeb Kumar Sah; Anais Bash-Taqi; Augustus Osborne (BMC Public Health)
Abstract Background Sierra Leone, like many developing countries, faces challenges in providing comprehensive sexuality education to its students. Despite the growing recognition of the importance of comprehensive sexuality education in promoting sexual health and well-being, there is a lack of standardised and accessible programs in many parts of the country. This study examined the disconnect between students’ needs (both perceived and real), their knowledge, and their preferences for delivering comprehensive sexuality education in Sierra Leone. Methods This qualitative study, which was part of a broader research initiative by the Institute for Development and funded by the UK Foreign Commonwealth Development Office, explored the delivery of comprehensive sexuality education in Sierra Leone. Using purposive sampling, the study engaged students, educators, school administrators, community leaders, and parents/guardians from 11 diverse schools across four provinces (Northern, Northwestern, Southern, and Western Area) in Sierra Leone. Data were collected through gender-separated focus group discussions and semi-structured interviews, conducted in schools and community settings, with protocols tailored to ensure cultural sensitivity and participant comfort. Thematic analysis was employed to identify patterns and themes related to students' comprehensive sexuality education knowledge, preferences, and contextual challenges. Results Our study reveals a hostile educational environment, with reports of male teachers making inappropriate advances and harassing female students, creating unsafe learning conditions. Economic challenges force many rural students to relocate to urban areas, where financial instability drives them into relationships for survival, often exacerbated by parental encouragement for economic gain. Girls engaged in hawking face heightened risks of sexual abuse. Students demonstrate some knowledge of sexual and reproductive health, including family planning and contraceptives, but gaps remain, particularly in understanding puberty and menstrual health. Information sources are varied, including digital platforms, traditional media, and community figures, but often lack reliability. Preferences for comprehensive sexuality education delivery differ by gender and marginalised groups, with female students favouring confidential, female-led discussions, while male students seek structured, community-based approaches. Marginalised groups, including students with disabilities and pregnant students, emphasise the need for inclusive, non-judgemental support. Conclusion The findings underscore the need for safe, inclusive, and culturally sensitive comprehensive sexuality education in Sierra Leone. Addressing teacher harassment and creating safe learning environments are critical, alongside tackling economic vulnerabilities that push students into exploitative relationships through financial support mechanisms. Bridging knowledge gaps on puberty and menstrual health requires improved curricula and teacher training, while reliance on informal sources highlights the need for accurate, youth-friendly information through trusted channels like female teachers and digital platforms. Tailored approaches for marginalised groups, such as students with disabilities and pregnant students, are essential, emphasising inclusive strategies like visual aids and community-based support.